Changing How Biologists View Flowers—Color as a Perception Not a Trait - Garcia, Jair E.; Phillips, Ryan D.; Peter, Craig I.; Dyer, Adrian G. (Frontiers in Plant Science, 2020)
Studying flower colour evolution can be challenging as it may require several different areas of expertise, ranging from botany and ecology through to understanding colour sensing of insects and thus how they perceive flower signals. Whilst studies often view plant-pollinator interactions from the plant’s perspective, there is growing evidence from psychophysics studies that pollinators have their own complex decision making processes depending on their perception of colour, viewing conditions and individual experience. Mimicry of rewarding flowers by orchids is a fascinating system for studying the pollinator decision making process, as rewarding model flowering plants and mimics can be clearly characterised. Here, we focus on a system where the rewardless orchid Eulophia zeyheriana mimics the floral colour of Wahlenbergia cuspidata (Campanulaceae) to attract its pollinator species, a halictid bee. Using recently developed psychophysics principles, we explore whether the colour perception of an insect observer encountering variable model and mimic flower colour signals can help explain why species with non-rewarding flowers can exist in nature. Our approach involves the use of colour discrimination functions rather than relying on discrimination thresholds, and the use of statistical distributions to model intraspecific colour variations. Results show that whilst an experienced insect observer can frequently make accurate discriminations between mimic and rewarding flowers, intraspecific signal variability leads to overlap in the perceived colour, which will frequently confuse an inexperienced pollinator. This new perspective provides an improved way to incorporate pollinator decision making into the complex field of plant-pollinator interactions.